Joeropsididae Nordenstam, 1933 (Crustacea, Isopoda, Asellota) from the Lizard Island region of the Great Barrier Reef, Queensland, Australia - Niel L. Bruce (ZooKeys, 2015)
The marine isopod family Joeropsididae (Asellota) is documented for the Lizard Island region of the Great Barrier Reef, Australia. Fifteen species of Joeropsis are recorded, including ten new species; descriptive notes are provided for five species that lacked adequate material for description. A revised family and genus diagnosis is presented together with comments on the most useful characters for species identification and a key to Joeropsis of the Lizard Island region.